ОСОБЛИВОСТІ ВИКОНАННЯ ТЕХНІЧНОГО РИСУНКА МЕТОДАМИ КРЕСЛЕННЯ (Педагогіка вищої та середньої школи, 2007)
Similarity and difference o f artistic and technical designs and also some particularities of fulfilling technical design in the drawing studies for the purpose of improvement o f perception of technical design characteristic features by the students of artisticorientation were considered in the article.